Coal ash fusion properties from molecular dynamics simulation: the role of calcium oxide. (15th March 2018) - Dai, Xin; Bai, Jin; Huang, Qing; Liu, Zhen; Bai, Xiaojing; Lin, Cheng-Te; Li, Wen; Guo, Wenping; Wen, Xiaodong; Du, Shiyu
Highlights: The lower melting temperature of anorthite relative to mullite is attributed to the difference in oxygen bond species between these two minerals. The major role of CaO is the debonding of Al-O in Al2 O3 -SiO2 -CaO amorphous systems because calcium is inclined to interact with Al-O bond. Abstract: The role of calcium oxide on ash fusion properties was investigated in this work by molecular dynamics simulations and thermodynamics calculations. The variation of volume was used to identify the melting points, which was compared with the liquidus temperature calculated by the FactSage codes. The phase diagram was calculated to explain the variation of melting points with the content of calcium oxide. The radial distribution functions and species of oxygen bonding were employed to characterize the structural evolution with the different fraction of calcium oxide. The melting point of anorthite is lower than that of mullite due to less tricluster oxygen atoms. The content of CaO with high flux efficiency in (SiO2 )2 -Al2 O3 -CaO is found from 5.00% to 15.00%. The current modelling work on melting behaviors of minerals containing various amount of CaO may provide new insight into the mechanism of ash fusion influenced by flux.